2019
DOI: 10.1042/bcj20180615
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between plants and soil shaping the root microbiome under abiotic stress

Abstract: Plants growing in soil develop close associations with soil microorganisms, which inhabit the areas around, on, and inside their roots. These microbial communities and their associated genes — collectively termed the root microbiome — are diverse and have been shown to play an important role in conferring abiotic stress tolerance to their plant hosts. In light of growing concerns over the threat of water and nutrient stress facing terrestrial ecosystems, especially those used for agricultural production, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
167
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(171 citation statements)
references
References 214 publications
(283 reference statements)
3
167
0
1
Order By: Relevance
“…Actinobacteria are grampositive (G + ), monoderm bacteria. G + bacteria are thought to accumulate under drought, and the cell wall is thought to improve cell drought tolerance by increasing their ability to resist desiccation [6,46]. Our data also show that G + bacteria were signi cantly enriched in the rhizosphere under drought conditions (Fig.…”
Section: Figure 6 Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Actinobacteria are grampositive (G + ), monoderm bacteria. G + bacteria are thought to accumulate under drought, and the cell wall is thought to improve cell drought tolerance by increasing their ability to resist desiccation [6,46]. Our data also show that G + bacteria were signi cantly enriched in the rhizosphere under drought conditions (Fig.…”
Section: Figure 6 Discussionsupporting
confidence: 64%
“…Similarly, Santos-Medellín et al reported root-associated community in rice in which several OTUs belonging to the phyla Actinobacteria and Chloro exi were signi cantly enriched under drought, whereas OTUs from the phylum Acidobacteria and classes Deltaproteobacteria were generally depleted [42]. Of note, many works focusing on the root bacterial microbiomes of rice [42], sorghum [43], and diverse lineages of plant species [44,45] under drought stress have reported enrichment of bacteria from the phylum Actinobacteria [6]. Actinobacteria are grampositive (G + ), monoderm bacteria.…”
Section: Figure 6 Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Western diet versus Mediterranean or vegetarian diet) [18] or addition of specific nutrients such as resistant starch [19]. In plants, alterations in soil microbiomes happen in response to biotic and abiotic stresses, such as those listed above [20]. More than one hundred dysbioses have been related to human diseases [21], and disease-suppressing soils -defined by their microbial composition -are studied to promote plant resistance to pathogens [22].…”
Section: Microbiome Dynamicsmentioning
confidence: 99%